Xylem embolism in new wilt of cotton - K.C. MANDLOI; M.L. NAYAK, P.P. SHASTRY, R.H. BALASUBRAMANYA, K.M. PARALIKAR, A. KRISHNA, U.S. MISHRA (Indian Phytopathology, 2002)
Xylem emboli were formed in root, stem and petiole portions of new wilt affected cotton whether the plants were grown in dry or water logged conditions in India. In revived plants, the emboli either disappeared or reduced in size. The diam. of xylemvessels was larger in affected plants compared with those from healthy plants.